1988
DOI: 10.2170/jjphysiol.38.159
|View full text |Cite
|
Sign up to set email alerts
|

Intramitochondrial inclusions caused by depletion of creatine in rat skeletal muscles.

Abstract: Effect of Creatine depletion by fl-guanidinopropionic acid (/3-GPA) feeding on mitochondrial morphology was studied in rats. Following /3-GPA feeding for 9 weeks, intramitochondrial inclusions running parallel to the long axis of mitochondrion were observed in skeletal muscles. A bundle of inclusions consisted of four parallel arrays containing electron-dense materials. Two outer arrays were continuous with cristal membranes and two inner arrays were chains of fine particles. Mitochondria with such inclusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…18.6 (SD 8.9) and 10.2% (SD 10.1) (Figure S1) [23][25], [28], [29], [34], [36], [43], [45], [48]–[50], [53], [54], [57], [59], [76], [82]. This apparent shift towards oxidative metabolism was accompanied by a 2-fold increase in mitochondrial DNA [20], and increased mitochondrial density [56], [78], with occasional subsarcolemmal accumulation of enlarged, elongated, or irregular shaped mitochondria, containing paracristalline inclusions [48], [54], [74], [81], [85], [86]. The paracrystalline inclusions, in some studies, were found to be condensed and crystallized mitochondrial CK [54], [86].…”
Section: Resultsmentioning
confidence: 99%
“…18.6 (SD 8.9) and 10.2% (SD 10.1) (Figure S1) [23][25], [28], [29], [34], [36], [43], [45], [48]–[50], [53], [54], [57], [59], [76], [82]. This apparent shift towards oxidative metabolism was accompanied by a 2-fold increase in mitochondrial DNA [20], and increased mitochondrial density [56], [78], with occasional subsarcolemmal accumulation of enlarged, elongated, or irregular shaped mitochondria, containing paracristalline inclusions [48], [54], [74], [81], [85], [86]. The paracrystalline inclusions, in some studies, were found to be condensed and crystallized mitochondrial CK [54], [86].…”
Section: Resultsmentioning
confidence: 99%
“…However, as noted previously it is clear that these muscle adaptations induced by ␤-GPA feeding were not related to increased muscle activity, since the EMG levels were significantly depressed in these animals. An increase in mitochondrial mass, often associated with intramitochondrial inclusions observed in myopathies has been observed following ␤-GPA feeding [36]. Moerland et al [20] reported that the total oxidative capacity of the EDL in ␤-GPA-fed mice was decreased because of a smaller muscle mass, even though the specific activities (per gram of muscle weight) of mitochondrial enzymes such as cytochrome oxidase and citrate synthase were higher than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Intramitochondrial inclusions in skeletal muscle, but not in heart muscle, have been reported in vivo, where rats had been fed with the creatine analogue B-GPA, which is known to cause creatine and phosphocreatine depletion in muscle (31). It was then of interest to test if B-GPA could interfere with the creatine effect in mitochondria of ARC described above, and in some way could restore the standard "creatinefree" culture conditions.…”
Section: The Creatine Effect Is Counteracted By the Creatine Analoguementioning
confidence: 99%
“…Although no indication exists as to how directly creatine brings about the effects on the mitochondria, its involvement is clearly demonstrated by experiments, where the creatine analogue/3-GPA reversed the creatine effect by competition in ARC, previously grown in creatine-substituted medium. Ohira et al (31) also had investigated the influence of/3-GPA in vivo on the ultrastructure of mitochondria in skeletal muscle from rabbits previously fed with the drug and observed similar mitochondrial inclusions in skeletal but not in cardiac muscle of animals chronically treated with the drug. Other authors have demonstrated that in vivo feeding of/3-GPA lowers the level of total creatine (creatine plus phosphocreatine) in muscle (26,50), because it inhibits creatine entry into muscle from the blood plasma (14,49).…”
Section: Effects Of Creatine and Of The Creatine Analogue B-gpamentioning
confidence: 99%
See 1 more Smart Citation